2021
DOI: 10.7150/thno.56157
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet, gut microbiome and gastrointestinal cancer

Abstract: Gastrointestinal cancer is currently one of the main causes of cancer death, with a large number of cases and a wide range of lesioned sites. A high fat diet, as a public health problem, has been shown to be correlated with various digestive system diseases and tumors, and can accelerate the occurrence of cancer due to inflammation and altered metabolism. The gut microbiome has been the focus of research in recent years, and associated with cell damage or tumor immune microenvironment changes via direct or ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 255 publications
(171 reference statements)
1
50
0
Order By: Relevance
“…Compared with the microbial prediction model, the metabolism model demonstrated higher test efficiency, which was consistent with the fact that the intestinal metabolites were more closely related to thyroid cancer in this microenvironment (32). However, since research on the influence of gut microbiota and metabolism in thyroid cancer is rare, further studies are required to establish a complete microenvironment diagnosis model (11).…”
Section: Discussionsupporting
confidence: 61%
“…Compared with the microbial prediction model, the metabolism model demonstrated higher test efficiency, which was consistent with the fact that the intestinal metabolites were more closely related to thyroid cancer in this microenvironment (32). However, since research on the influence of gut microbiota and metabolism in thyroid cancer is rare, further studies are required to establish a complete microenvironment diagnosis model (11).…”
Section: Discussionsupporting
confidence: 61%
“…This result suggests the negative relationship between Lachnospiraceae and inflammation, which is in line with previous study in mice [ 32 ]. Previous studies have shown that HFD can significantly alter the composition of gut microbes [ 36 ]. HFD might lead to increased hepatic retention of hydrophobic bile acids, which are significantly associated with changes in intestinal microorganisms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a public health problem, a high-fat diet has been shown to be associated with various digestive system diseases, cardiovascular diseases, urinary system diseases, tumors, etc. and can accelerate the occurrence of diseases due to inflammation and metabolic changes ( Yin et al., 2018 ; Tong et al., 2021 ). A high-fat diet is closely associated with changes in the gut microbiota.…”
Section: The Gut Microbiota In the Pathogenesis Of Hua And Goutmentioning
confidence: 99%